Smart strategic transformation of Changhong - Meng, Fei, active 2015; McFarlan, F. Warren. (Franklin Warren); Mao, Bo (London : Tsinghua University School of Economics and Management, 2015)
In 2004, Zhao Yong officially took over as Chairman and General Manager of Sichuan Changhong Electric Co., Ltd. (Changhong). Facing fierce competition in domestic and international consumer electronics markets and many difficulties and challenges in Changhong's development, Zhao Yong proposed a "Three Coordinates" strategy and implemented bold reform in corporate strategy, industrial structure and organization systems. The need to improve operational and management efficiency forced Changhong to invest substantially in informatization.In recent years, many new things in the Internet industry, such as cross-border competition, cloud computing, big data and O2O (online to offline commerce), are profoundly influencing the home appliance industry. To cope with changes in the home appliance industry in the "post-PC" era, in 2013, Zhao Yong updated the "Three Coordinates" strategy into a "New Three Coordinates" strategy which focused on "intelligence, network and collaboration", and launched the CHiQ series, smart black-and-white home electric/electronic appliances that aimed to "overturn the traditional product concept". It has been many years since Changhong lose its leadership in home appliances. Can Changhong regain its leadership with Zhao Yong's new strategy?
Originally published in Meng, F., McFarlan, F. W., & Mao, B. (2015). Smart strategic transformation of Changhong. 2015-11-30. Beijing: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Zhao, Yong, -- 1963-; Sichuan Changhong Electric Co., Ltd; Household appliances industry -- China -- Management -- Case studies